Pharmacokinetics of Menthol and Carvone after Administration of an Enteric Coated Formulation Containing Peppermint Oil and Caraway Oil - Mascher, Hermann; Kikuta, Christian; Schiel, Helmut (Arzneimittelforschung, 2001)
Enteric coating of peppermint oil/caraway oil capsules avoids subjective discomfort to the patient caused by gastroesophageal reflux. In order to confirm bioequivalence of an enteric coated formulation containing peppermint oil and caraway oil (CAS 277309-55-4, Enteroplant®) and an immediate release formulation of both oils, the pharmacokinetics of menthol and carvone after oral administration of the two formulations were studied in a randomized, two-period cross-over study in 16 healthy male volunteers. The subjects received 180 mg peppermint oil and 100 mg caraway oil, once as 2 enteric coated capsules of the fixed enteric coated combination preparation containing 90 mg peppermint oil (WS® 1340) and 50 mg caraway oil (WS® 1520) each (test) and once in the form of 5 capsules of an immediate release formulation (reference) containing 36 mg peppermint (WS® 1340) oil and 20 mg caraway oil (WS® 1520) each. The capsules were taken with 250 ml water after a 10 h fast. Both substances were determined in plasma by GC/MS after extraction. The limit of quantification was 10 ng/ml for menthol and 0.5 ng/ml for carvone. The mean maximum plasma levels for menthol were 1196 ng/ml after administration of the test medication and 1492 ng/ml after administration of the reference medication. The bioavailability with respect to the AUC was comparable after administration of test and reference preparation, the 90 % confidence interval was 97 to 105 %. As expected, there were considerable differences for Tmax. After application of the enteric coated form the maximum concentration was reached significantly later (3.0 h vs. 1.7 h) compared to the immediate release capsule. Corresponding data were also calculated for carvone. After application of the test medication the maxima of 14 ng/ml for both formulations were reached later (2.5 h vs. 1.3 h). The 90 % confidence interval of the AUC for carvone was 79 to 119 % and therefore slightly outside the acceptable range for bioequivalence of 80 to 125 %. However, this fact should not be relevant, in particular since the dosage of the enteric coated capsule lies at the upper limit of the model text and positive clinical studies, also on the therapeutic equivalence of the two formulations, are available.
Keywords: Caraway oil; Carvone; CAS 277309-55-4; Enteroplant®, clinical pharmacokinetics; Menthol; Peppermint oil; WS® 1340; WS® 1520